Faktor-Faktor yang Memengaruhi Keputusan Pemilihan Kosmetik pada Anggota Subunit Tari Universitas Negeri Jakarta - Kartika Rahma Dewi Mahardika; Eti Herawati; Lilis Jubaedah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Selecting stage cosmetics requires specific considerations because the products must support character portrayal, facial expression, and makeup durability throughout a performance. This study aimed to analyze the effects of product quality, price, and promotion on cosmetic selection decisions among members of the Dance Subunit of the Student Arts Unit at Universitas Negeri Jakarta. A quantitative approach with a cross-sectional survey design was employed. All 30 active members of the Dance Subunit were included as respondents through total sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using multiple linear regression, t-tests, an F-test, and the coefficient of determination with SPSS. The results showed that product quality had a positive and significant effect on cosmetic selection decisions (t = 2.361; p = 0.026), whereas price had no significant effect (t = 0.137; p = 0.892). Promotion had a positive and significant effect and was the strongest predictor (t = 4.299; β = 0.679; p < 0.001). Simultaneously, product quality, price, and promotion significantly affected cosmetic selection decisions (F = 25.054; p < 0.001). These variables explained 74.3% of the variance in cosmetic selection decisions. The findings indicate that stage cosmetic selection decisions are primarily determined by product quality and promotion, while price is not a significant independent determinant.